(untitled) (Bangladesh Journal of Zoology, 2016)
Checkered Keelback, Xenochrophis piscator, was found to inhabit aquatic, semi-aquatic, terrestrial and fossorial habitats. The average body weight of Checkered Keelback was 233 ± 107.25 g. The average weight of the consumed food by each animal was 10.28 ± 6.78 g, which was 4.41% of their body weight. A total of 23 food items were found in the stomachs of 40 snakes. All the food items were animal food, but three categories of accidental food items were found in the stomachs. Based on food contents the snake fed mainly on arthropods (56.52%), fish (26.80%) and amphibians (17.39%). The consumption of food varied seasonally, being much less in winter compared to summer and rainy seasons but the per cent frequency of occurrence of insects in relation to the total number of food items was more or less the same in all seasons. Insects belonged to 14 families under seven orders, mostly harmful to agriculture, fish ponds, gardens and human residences. Bangladesh J. Zool. 44(1): 153-161, 2016